66.9k views
6 votes
Solve the following problem:

5x - 3 = 4x + 3

A. x = 5

B. x = 6

C. x = 7

User StuXnet
by
5.4k points

2 Answers

7 votes

Answer:

B.

Explanation:

5x-3+3=4x+3+3

5x=4x+6

5x-4x=4x+6-4x

x=6

User Manu Benjamin
by
5.5k points
2 votes

Answer:

x=6

Explanation:

Step 1: Subtract 4x from both sides.

5x−3−4x=4x+3−4x

x−3=3

Step 2: Add 3 to both sides.

x−3+3=3+3

x=6

User AndroGuy
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.